Temporal Effect of Muscle Contraction on Respiratory Sinus Arrhythmia - Nakamura, Y.; Hayashi, N.; Muraoka, I. (Methods of Information in Medicine, 1997)
The purpose of this investigation was to compare the heart rate variability at respiratory frequency (HRVRF) in muscle contractions during the inspiratory phase with that during the expiratory phase. Eight volunteers performed pedaling on a cycle ergometer, twice a cycle of respiration (4 sec) against a load of 0.25 Nm/kg BW, of which the timing was adjusted to twice during the inspiration phase (I), once during the expiration, once during the inspiration (El), or twice during the expiration phase (E). Spectral analysis was applied to the R-R intervals of each condition. The amplitude of HRVRF in E was less than half of I (9 ± 2 msec versus 23 ±2 msec). The results indicate that the timing of muscle contraction can affect the heart rate variability even at the frequency band of respiration.
Keywords: Parasympathetic Nervous Activity; Respiratory Sinus Arrhythmia; Respiratory Phase; Heart Rate Variability